O gênero debate no ensino fundamental: uma vivência de ensino-aprendizagem mediada pelas sequências didáticas - Silva, Gracilene Barros da (2016)
This dissertation it is a research of qualitative nature and applied, descriptive character and interventionist, that aimed to describe and analyze the process of oral production genre debate of controversial fund opinion mediated by the didactic sequences, with the focus on sociodiscursivas characteristics of the genre. The survey was conducted in a class of eighth-graders (elementary school), with 41 students, between 11 and 17 years, entered into a school in the State schools, located in the city of Santa Rita-PB. Specifically, it is a survey carried out in the classroom about the teaching of Genre Debate Mediated by the Didactic Sequences in a Sociointeracionista perspective, based on studies of Bakhtin (2011 [1979]), with regard to discursive genres, and in studies of Dolz et al. (2013a), with the design of the genre as a tool for teaching and learning to use social language practices. In this perspective, we approach the teaching of genre by adopting the procedure of the didactic sequences, from the perspective of Dolz, Noverraz and Schneuwly (2013c), offering work in the genre modules, either as oral, with focus on the advances and difficulties presented by the students by using the aforementioned genre. With regard specifically to the teaching of the debate, we rely on the contributions of Dolz, Schneuwly and Pietro (2013b). In this sense, the analysis had as corpus both oral productions made by students involved in the investigation, held before the intervention by means of modules, and another after the intervention. On analysis of initial production, we detect problems related to the structure of the genre-difficulties in General Organization of the debate and in the performance of the members in connection with their roles in the use of the genre; the informatividade-low argumentatividade and little use of textual reconstruction strategies; and, in relation to the appropriateness of the language in the style of debate-the use of inappropriate words in the style of genre and the manifestation of biased behaviour regarding the use of non-default variant in the production of the debate. These difficulties were worked by means of modules, as proposes the following procedure. After this intervention, was held the production end of the debate, which allowed us to verify that the problems detected in the first production were minimized. So, we were able to ascertain that the difficulties presented in relation to the structure, the informatividade and the suitability of language in the style of genre are minimized. Students have developed sociodiscursivas skills such as the use of argumentative strategies and textual reconstruction that were important for effective interaction in the use of the genre. In this sense, the education debate by means of didactic sequences, in addition to developing sociodiscursivas skills important for interaction, instrumentalizou students to use the debate effectively.